Health risks and environmental impacts of domestic wastewater at Adétikopé (Togo, West Africa) - Gbekley, Efui Holaly; Komi, Kossi; Poli , Sossawè; Gbekley, Abla -Sika Hanou; Adjoussi, Pèssiezoum (Edelweiss Applied Science and Technology, 2024)
The demographic growth rate of the locality of Adétikopé causes a problem of management of waste water, sanitation, health and especially habitat. The densification of populations in these types of municipalities causes health problems linked to environmental degradation. The objective of this study is to identify the consequences (socio-sanitary and environmental impacts) caused by the poor management of wastewater in the peri-urban municipality of Adétikopé and to propose solutions. From August 2022 to July 2023, we undertook a socio-sanitary survey within the households of the commune using semi-structured questionnaires and interviews with health and communal officials. To this was added participant observation in the neighborhoods of the municipality. Thus, the frequencies of malaria and anemia are linked to poor management of water and household waste. Respiratory infections are due to unsanitary housing and air pollution. The populations of these generally deprived neighborhoods have little information on the relationship and the implication of the state of the environment on their health problems so that they are not very interested in the man-agement of their living environment. The recommended solutions in-clude, among other things, the use of impregnated mosquito nets and the use of hygiene and sanitary techniques.